1988
DOI: 10.1021/j100334a049
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of interfacial charge transfer in iron(III) oxide colloids

Abstract: differing greatly in doping density. Electrodes with the largest doping densities (>1019 cm"3) yield anomalous impedance, kinetic current, and photopotential behavior. Kinetic current vs potential curves for redox couples with similar structure and reorganization energy but different reduction potentials indicate that different mechanisms are responsible for electron transfer across the WSe2/acetonitrile interface. Exchange current densities are not in close agreement with the predictions of commonly used theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…In these control experiments, there was no measurable shift in the soluble viologen concentration before and after the addition of the oxide, indicating that no sorption was occurring. Similar observations have been made in previous studies which used viologen and iron oxides(149,157,159). In all experiments, the amount of viologen added to a reactor was known, allowing for comparison between the theoretical and experimental total viologen concentrations; the viologen concentration was typically within 10 % of the expected value, with no bias in either direction (i.e., no consistent over-or under-estimation)(Tables 5.1-5.3).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…In these control experiments, there was no measurable shift in the soluble viologen concentration before and after the addition of the oxide, indicating that no sorption was occurring. Similar observations have been made in previous studies which used viologen and iron oxides(149,157,159). In all experiments, the amount of viologen added to a reactor was known, allowing for comparison between the theoretical and experimental total viologen concentrations; the viologen concentration was typically within 10 % of the expected value, with no bias in either direction (i.e., no consistent over-or under-estimation)(Tables 5.1-5.3).…”
supporting
confidence: 66%
“…Previous work in the field of photochemistry has utilized soluble radical redox probes to determine the redox state of the solution (149,(154)(155)(156)(157)(158)(159). The viologens (4,4'-Bipyridine and its substituents) are commonly used due to their pH-independent oneelectron reversible redox potentials which can be manipulated with functional groups (155,160).…”
Section: Resultsmentioning
confidence: 99%
“…A similar approach was used by Mulvaney et al [44] to study interfacial charge transfer in Fe(III) colloids (hematite and goethite nanoparticles). Instead of AQDS they used radiolytically produced organic radicals.…”
Section: Redox Potential Of Fe(ii) Sorbed To Ferric Hydroxidesmentioning
confidence: 99%
“…It appeared that the rate of electron transfer is governed by the free energy difference between the redox potential of the redox couple in the electrolyte and the flatband potential in the solid as was demonstrated in radiolysis experiments with colloidal ferric oxides, that is, experiments where free radicals are produced to allow for electron transfer [44]. In these experiments, it was clearly demonstrated that aside from the quasi Fermi level, also the electrostatic interaction between the reducing radical and the electric double layer at the interface influenced electron transfer.…”
Section: The Semiconducting Properties Of Ferric (Hydr)oxidesmentioning
confidence: 99%
“…23 Earlier studies of iron oxide reduction using pulse radiolysis concluded that electron migration could cause indefinite trapping of electrons. 24 Thus, internal electron conduction could contribute to the overall reaction rates of iron oxide dissolution or recrystallization, but this contribution has never been quantified.…”
Section: ■ Introductionmentioning
confidence: 99%